Exposure to fipronil elevates systolic blood pressure and disturbs related biomarkers in plasma of rats - Chaguri, Joao Leandro [UNESP]; Godinho, Antonio Francisco [UNESP]; Horta, Daniel França [UNESP]; Gonçalves-Rizzi, Victor Hugo [UNESP]; Possomato-Vieira, Jose Sergio [UNESP]; Nascimento, Regina Aparecida [UNESP]; Dias-Junior, Carlos Alan [UNESP] (Elsevier, 2016)
Recent reports show that fipronil affects non-target organisms, including environmental species populations and potentially humans. We aimed to examine if fipronil exposure affects the systolic blood pressure and related biomarkers. Thus, fipronil was orally administered to rats (30 mg/kg/day) during 15 days (Fipronil group) or physiological solution (Control group). While fipronil increased significantly the systolic blood pressure (158 ± 13 mmHg), no significant changes were observed in Control group (127 ± 3 mmHg). Significantly, higher levels of fipronil in plasma were observed in Fipronil group (0.46 ± 0.09 μg/mL versus 0.17 ± 0.11 μg/mL in Control group). Fipronil group showed lower weight gain compared with Control group. While fipronil resulted in higher concentrations of endothelin-1, reduced antioxidant capacity and lower levels of circulating matrix metalloproteinase 2 (MMP-2) and nitric oxide (NO) metabolites compared to Control group, no alteration was observed in serum biomarkers of renal and hepatic/biliary functional abilities. Therefore, this study suggests that fipronil causes hypertension and endothelin-1 plays a key role. Also, these findings suggest that reductions of both MMP-2 and NO may contribute with the elevation of systolic blood pressure observed with fipronil.
Keywords: Biomarkers; Cardiovascular toxicity; Fipronil; Pesticides